ECONOMIC SECURITY OF CURRENCY DURING PANDEMIC PERIOD - D. Abakumova; E. Kalashnikova; K. Latchina (Вестник Северо-Кавказского федерального университета, 2022)
The article provides a description of the position of currencies in the financial market, reflecting the importance for the Russian economy. At the same time, financial activities and the dependence of the ruble exchange rate on oil prices, which give a general idea of its condition for today, are analyzed, as well as an analysis of the oil and gas sector of the economy and a forecast for the positive development of the economy in 2021. The search for the facets and role of financial management, oil prices and currency stability is determined. The conclusion is given on finding the border between liquidity, profitability and riskiness, which allows you to find the optimal ratio between these indicators. It tells about the development of currencies today, what they are undergoing significant changes, about quick adaptation to changes and the ability to rapidly move forward. On the economic security of currencies and current trends in the financial market.